Investigation of metaverse and music education - ARICI, İSMET (My University, 2024)
Metaverse can be defined as a virtual sharing space created by the integration of augmented reality, virtual reality and mixed reality technologies. Its applications in education are notable for its potential to provide students with personalized and adaptable learning experiences. Music education is constantly evolving as a result of technological advances and changing student needs. Metaverse opens a new dimension in the interaction and learning processes of students and teachers in music education. Metaverse has opened a new dimension in education by bridging the digital and physical worlds. Music education has also benefited from this innovative environment and enriched learning experiences thanks to virtual reality and augmented reality technologies. This study emphasizes that the importance of the metaverse in education has increased, especially after the pandemic, and that applications have diversified in different disciplines. A literature review was conducted for this research, which was conducted as a compilation study. “Metaverse and Education”, “Metaverse and Music”, “Augmented reality and Education”, “Virtual reality and Education” were used as keywords. Regarding the research content, 19 studies covering the period between 2015 and 2024 were used. In line with these studies, the subject was examined from an educator's perspective. Keywords: Metaverse, Education, Music Education, Metaverse and Music
Keywords: Sosyal ve Beşeri Bilimler; Sanat; Müzik; Müzik Bilimleri; Social Sciences and Humanities; Art; Music; Music Sciences; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; MÜZİK; SANAT; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; MUSIC; ART; Görsel Sanatlar ve Gösteri Sanatları; Müzecilik; Sosyal Bilimler ve Beşeri Bilimler; Visual Arts and Performing Arts; Museology; Social Sciences & Humanities; Metaverse; Education; Music Education; Metaverse and Music